The relationship between ego identity status and acculturation strategies (comparative study) - Ahmed Gamal Gawas; Aamer Aldbyani (Heliyon, 2024)
The present study aims to investigate the acculturation strategies employed by Yemeni students in Turkey and China, and their relationship with Ego identity status and perceived cultural distance. The study involved 506 Yemeni students enrolled in Turkish and Chinese universities, with 290 participants studying in Turkey (57.3 %) and 216 studying in China (42.7 %). The age of the participants ranged from 18 to 42 years, with a standard deviation of 5.45 and a mean of 27.34 years. The results indicated that the strategies adopted by Yemeni students were similar in both countries. Ego-identity states were found to be predictors of acculturation strategies. Identity achievement was found to predict integration strategy, while foreclosure identity predicted separation strategy. Additionally, identity moratorium and identity diffusion predicted the marginalization strategy. Knowledge of the host country's language was a predictor of willingness to integrate into the host society. The immigrant's lack of knowledge of the host country's language led them to adopt a separation strategy. Cultural distance was also found to be highly predictive of the assimilation and separation strategy. Furthermore, the presence of family members with the immigrants led to the adoption of tendencies to preserve the native culture, while immigrants living without their families in the host country tended to adopt the assimilation strategy.